INCREASING OF GLYCOSAMINOGLYCAN AND HYDROXYPROLINE CONTENT IN RAT CARTILAGE MANDIBLES AFTER INSULIN LIKE GROWTH FACTOR“I INDUCTION: PENINGKATAN GLIKOSAMINOGLIKAN DAN HIDROKSIPROLIN PADA TULANG RAWAN MANDIBULA TIKUS SETELAH INDUKSI INSULIN LIKE GROWTH FACTOR-I - I Gusti Aju Wahju Ardani (Dentika: Dental Journal, 2012)
The cellular effects of Insulin Like Growth Factor-I (IGF-I) are mediated by binding to cell IGF-I receptors, which are found mainly on cells of mesenchymal origin, such of fibroblast, chondrocytes, and osteoblast. The study suggests that IGF-I may regulate chondrocytes proliferation, differentiation and extracellular matrix deposition. The purpose of this study was to quantify a synthesis of hydroxyproline HYP and glycosaminoglycan (GAG) by primary chondrocyte culture with IGF-I at 0, 5, 25, and 50 ng/ml concentration. Chondrocyte proliferation was assessed with collagen synthesis and measured by using hydroxyproline (HYP) assay and glycosaminoglycan GAG synthesis was determined with dimethylmethylene blue dye binding assay for 10 days. Primary chondrocytes was cultured for 10 days with 0, 5, 25 and 25 ng/ml IGF-I. The results showed that, IGF-I was a potent in increasing GAG synthesis and also effective in promoting collagen HYP synthesis. At the 50 ng/ml concentration, IGF-I was upregultators of GAG synthesis, producing 6 times more GAG than control. Collagen content was promoted by IGF-I at its lower concentration, with level 3 times higher than control. In conclusion, IGF-I at doses ranging from 5 to 50 ng/ml for ten days has proved the induction GAG and HYP synthesis in 10 days primary chondrocyte culture of secondary cartilage rat condyles.